Expression of neighboring and followers In the car (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the best of messengers, Muhammad Al-Amin, and upon his good and pure family, and whoever clings to his religion and his honorable household until the Day of Judgment, and after: